(untitled) (Journal of Bangladesh Academy of Sciences, 2014)
Fiber reinforced polymer composites played a dominant role in a variety of applications for their high specific strength and modulus. The present work describes the effects of palm fiber addition on physico-mechanical properties of polyvinyl chloride (PVC) composites. The tensile strength and Youngs modulus of the fabricated products increased, while the bulk density, flexural strength and tangent modulus decreased with the increase of fiber addition. The tensile strain decreased with the increase of fiber addition up to 10% and after that it remained nearly constant, while flexural strain remained increasing. There was an initial differential thermal analysis (DTA) peak for both palm fiber and composite, whereas PVC did not have that peak due to water absorption. Thermal analysis of PVC-palm fiber composites has shown that thermal degradation of PVC started ahead of palm fiber. The thermal stability of composite was found to be the average of palm fiber and PVC foam sheet DOI: http://dx.doi.org/10.3329/jbas.v38i1.20215 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 1, 83-92, 2014